Uphicotho lweencwadi zabantwana ezikhethiweyo eziguqulelwe esiXhoseni - Madolo, Yolisa (Rhodes University, Faculty of Humanities, School of Languages, 2020)
Appraisal of African languages' children's literature and its translation seems to be developing at a slow pace. This literary genre seems to be the last on the literary critics' list. As a result, children's literature translators seem to do as they please, with no fear that there is someone to critique the work. Translation for children is more than just literary translation, because it is meant for a special audience, whose language skills are still developing. The translator, therefore, needs to be someone dedicated in target language development. This translation needs a translator with a deep knowledge of both the source and target languages and their cultures. This will result in a translation that is readable and acceptable in the target language. The aim of this study was to critically analyse 20 selected isiXhosa translated stories, looking at how they have been translated in order to sound original in the target language. A sample of five stories were taken and analysed looking at their macrostructure. The findings of the analysis were that the isiXhosa stories resembled the English ones. Even the equivalence of the translated versions showed that the translation transferred the message in the source texts. However there were challenges as indicated. The study was done using Skopos theory, which advocates for the translator to always keep their audience in mind. It suggests that the translator should always strive for a translation that is acceptable to the target language. Various strategies can be used by the translator to fulfil this. Some of the strategies found to have been used in the translations are adaptation through omission, addition, addition of target culture specific terms, and changing sentence mode. Generally, the source language message seems to have been successfully transferred to the target language. However, errors in some stories were a cause for concern, as they could deter the target reader's interest in the stories. Such errors are spelling mistakes, word division errors, incorrect concord use, etc. These errors are a matter of concern in literature, more especially children's literature where children are still developing their reading skills.
Keywords: Children's literature, -- South African; Xhosa fiction -- Juvenile literature; Xhosa language -- Juvenile literature; Translating and interpreting in literature; Xhosa literature; Xhosa language -- Translating